2015
DOI: 10.1097/tp.0000000000000662
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Neutral Protease and Clostripain on Rat Pancreatic Islet Isolation

Abstract: Clostripain had a strong synergistic effect with ChNP, but not with TL. Therefore, ChNP and CP, in combination with collagenase derived from the same bacteria, may effectively increase the isolation efficiency without affecting the quality of islets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 32 publications
0
27
1
Order By: Relevance
“…Pancreatic islet transplantation is currently regarded as one of the treatment options for severe diabetes. 26 Considering that the clinical applications of HTx remain limited, 2,7 a number of experiences originating from islet transplantation, including cell isolation methods, 21,27,28 culture systems, 21,29 cell preservation, 18,21,22 cell graft evaluation, 30-32 and engraftment 33-35 could be applicable for improving the outcomes of HTx. Per the above-noted concepts, in the present study, the TD was applied to hepatocytes and was found to be effective for maintaining the viability and function of hepatocytes during a short-term preservation period.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic islet transplantation is currently regarded as one of the treatment options for severe diabetes. 26 Considering that the clinical applications of HTx remain limited, 2,7 a number of experiences originating from islet transplantation, including cell isolation methods, 21,27,28 culture systems, 21,29 cell preservation, 18,21,22 cell graft evaluation, 30-32 and engraftment 33-35 could be applicable for improving the outcomes of HTx. Per the above-noted concepts, in the present study, the TD was applied to hepatocytes and was found to be effective for maintaining the viability and function of hepatocytes during a short-term preservation period.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant clostridial collagenases, ColG and ColH, were obtained from Meiji Seika Pharma Co., Ltd. (Tokyo, Japan). The recombinant CP was purified as described previously (Dendo et al 2015). Collagenase V (Sigma-Aldrich Co.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study in rats confirmed these previous observations, and found nearly triplicated islet yields when collagenase and neutral protease were additionally supplemented with clostripain. Interestingly, combining clostripain with TL did not enhance islet yield, and resulted in increased islet fragmentation in contrast to the combination with neutral protease [80]. An incompatibility between TL and clostripain extracted from different species is assumed to cause the problem.…”
Section: Enzyme Characterizationmentioning
confidence: 99%